IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH DEBATE TECHNIQUE - Reni Rosianna Lumbangaol; Muhammad Rizki Mazali (University of Muhammadiyah Malang, 2020)
Lecturers can use many strategies to improve speaking ability. Speaking abilities include making questions, providing explanations, and also being able to provide answers. This study aimed to determine how debate techniques can improve students' speaking ability to make questions, give explanations, and give responses. The current study applied the classroom action research method and consisted of 3 cycles. Two batches of English Education College Students of 2019/2020 at Universitas Potensi Utama, totaling 60 students, were involved as the study subjects. An observation checklist and field notes were used to collect the data. The researchers observed students' activity in the classroom by using an observation checklist and fieldnotes. The researchers summarized the problem during the debating process. Based on the research findings, the debate technique applied by the research subjects reflects the improvement in the students' speaking ability. Based on the observations' results, it can be seen that the students' speaking ability in making questions and providing explanations and answers improved. The students' activities in the class when arguing in the first cycle were 42.83%, 59.17% in the second cycle, and 85.17% in the final one. It shows that the debate technique has improved the students' speaking ability to make questions and provide explanations.